Endoscopic Ultrasound Findings in Duodenal Gangliocytic Paraganglioma - Shyr-Ming Sheen-Chen; Tung-Lung Tsai; Hock-Liew Eng (Canadian Journal of Gastroenterology)
Gangliocytic paraganglioma is an uncommon benign neurogenic tumour of the digestive tract that is usually located in the descending duodenum. Due to the unusual location, such lesions are frequently overlooked on routine radiological examinations and initial endoscopy. With the recent development of endoscopic ultrasound, lesions in this location can be more easily detected and better viewed. A case of a duodenal gangliocytic paraglioma detected by endoscopic ultrasound is presented; this is possibly only the second such case to be reported in the literature.